Peningkatan Kapasitas Sink pada Tanaman Melon (Cucumis melo L.) dengan Pemberian Giberelin - Siti Fatonah; Musliar Kasim; Auzar Syarif (Universitas Riau, 2009)
For cultivation of melon (Cucumis melo L.), farmers only keep one fruit per plant to maintain quality fruit. To improve productivity, one possible effort is by spraying gibberellins at melon in combination with increasing amount of fruit maintained for each plant. The aim of this study was to know the effect of gibbereline in improving sink capacities of melon when fruit amount is increased. Gibberelins was sprayed at concentration of 0, 30, 60, and 90 mg/l to melon crop with different fruit amount per plant (one, two and three fruit). The study indicated that for melon plant with more than one fruit per plant, gibberellins application was not able to maintain the fruit quality, because the fruit weights were still decreasing. Thus, gibberellins application was not able to improve the sink capacities if fruit amount per plant is increased. While for plant with only one fruit, spraying 60 and 90 mg/l gibberellins can improve the fruit weight, so gibberellins improves the sink capacities if only one fruit is maintained for each plant.